Magnetic hyperthermia-induced drug release from ureasil-PEO-γ-Fe2O3 nanocomposites. Issue 68 (4th July 2016) - Caetano, B. L.; Guibert, C.; Fini, R.; Fresnais, J.; Pulcinelli, S. H.; Ménager, C.; Santilli, C. V.
Abstract : A multifunctional hybrid material suitable for cancer therapy, combining stimuli-responsive properties for drug delivery and magnetic hyperthermia. Abstract : A multifunctional material suitable for cancer therapy, which combines stimuli-responsive properties for drug delivery and magnetic hyperthermia prepared by a one-pot sol–gel synthesis from the conjugation of ureasil cross-linked poly(ethylene oxide) (U-PEO) hybrid materials with superparamagnetic nanoparticles (γ-Fe2 O3 ), is reported in this communication.